- #1

- 160

- 8

Solve the following equation with algebraic fractions

x/5 - (2x+4)/3 = 1

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter tomtomtom1
- Start date

- #1

- 160

- 8

Solve the following equation with algebraic fractions

x/5 - (2x+4)/3 = 1

- #2

Homework Helper

- 6,223

- 31

Expand out -(2x+4)/3 and then use your normal rules of algebra. Are you able to expand -(2x+4)/3 ?

- #3

- 160

- 8

is it 2x/3 + 4/3

- #4

Homework Helper

- 6,223

- 31

is it 2x/3 + 4/3

Right so (2x+5)/3 = 2x/3 + 4/3. If you put this into your equation you will have:

x/5 - (2x/3 +4/3) = 1

Can you simplify the left side of this equation using your standard algebra rules?

- #5

- 160

- 8

3x/15 - 10x/15 + 4/3

-7x/15 + 4/3 = 1

-7x/15 + 4/3 = 1

- #6

Homework Helper

- 6,223

- 31

3x/15 - 10x/15+ 4/3

-7x/15 + 4/3 = 1

For -(2x/3 + 4/3) you are essentially multiplying each term in the bracket by -1. So you should not have +4/3. What should you have instead? After you do that, make -7x/15 the subject of the formula.

- #7

- 160

- 8

3x/15 - 10x/15 - 4/3 = 1

-7x/15 - 4/3 = 1

-7x/15 = 1 + 4/3

-7x = (1+4/3)*15

-7x = 15+(60/3)

-7x = 35

x = 35/-7

x = -5

Thanks

Share:

- Replies
- 1

- Views
- 477

- Replies
- 10

- Views
- 173

- Replies
- 4

- Views
- 455

- Replies
- 8

- Views
- 1K

- Replies
- 1

- Views
- 543

- Replies
- 3

- Views
- 601

- Replies
- 5

- Views
- 572

- Replies
- 3

- Views
- 185

- Replies
- 26

- Views
- 654

- Replies
- 2

- Views
- 493